Determinan Niat dan Perilaku Merokok pada Remaja Berdasarkan Theory of Planned Behavior: Studi Literatur Tahun 2021–2025 - Manda Harisma (Barongko: Jurnal Ilmu Kesehatan, 2026)
Smoking behavior among adolescents remains a major public health concern at both national and global levels. Adolescents are particularly vulnerable to social and environmental influences, which increases their likelihood of initiating smoking at an early age. The Theory of Planned Behavior (TPB) has been widely applied to explain smoking intention and behavior through three core constructs: attitude toward the behavior, subjective norms, and perceived behavioral control. This study aims to systematically review the determinants of smoking intention and behavior among adolescents based on the TPB framework. A literature review method was employed by analyzing eight national and international journal articles published between 2021 and 2025. The findings indicate that smoking intention is the strongest predictor of actual smoking behavior as well as smoking cessation intention among adolescents. Positive attitudes toward smoking, permissive subjective norms particularly peer influence and low perceived behavioral control are consistently associated with higher smoking intention. Conversely, negative attitudes toward smoking and stronger perceived behavioral control contribute to higher intentions to quit smoking. These results highlight the robustness of TPB in explaining adolescent smoking behavior and emphasize the importance of developing preventive interventions that target attitude change, healthy social norm formation, and the strengthening of adolescents’ self-control abilities.